Strategies for Addresing Population Dynamics and Land Cover Change in Bukit Mangkol - Edo Bastian Jatmika; Edi Rusdiyanto; Lilik Sulistyowati (Information Technology and Science (ITScience), 2026)
The Bukit Mangkol Grand Forest Park (Tahura) in Central Bangka Regency, Bangka Belitung Islands Province, plays a vital ecological role as a biodiversity conservation area. However, rapid population dynamics in surrounding buffer zones have driven significant land cover changes within this conservation area. This study aimed to analyze the dynamics of population growth and its impact on land cover change, identify primary driving factors through Rapid Land Tenure Assessment (RaTA), and formulate resolution strategies using the Analytical Hierarchy Process (AHP). A mixed-methods approach was employed, integrating spatial analysis through Geographic Information Systems (GIS) using Landsat 7 ETM+, Landsat 8 OLI, and Sentinel 2A imagery from 2013 to 2023. Results revealed that the total population of Central Bangka Regency increased by 23.6%, from 167,000 in 2013 to 206,478 in 2023. Concurrently, secondary dry forest cover declined by 23.9% (from 1,462.1 ha to 1,113.16 ha), while plantation areas expanded by 186.7% (from 218.72 ha to 627.03 ha). RaTA analysis identified three primary factors influencing land cover change: ecological (land tenure insecurity), social (population growth in buffer zones), and economic (livelihood dependency on forest resources). AHP analysis showed that ecological factors received the highest priority weight (0.665), followed by economic (0.237) and social (0.098) factors. Recommended strategies include critical land rehabilitation and law enforcement (ecological), community participation through conservation partnership (social), and development of alternative livelihoods (economic).